Selected Experimental Tests of Materials Used in Rapid Prototyping Area - Novakova-Marcincinova, Ludmila; Novak-Marcincin, Jozef; Torok, Jozef; Barna, Jozef (Manufacturing Technology Journal, 2013)
Introduction into problems - Rapid Prototyping (RP) presents the automatic production of physical parts using by additive manufacturing technology. The start techniques for Rapid Prototyping became available in the late 1980s and were used to produce models and prototype parts. Today they are used for a much wider range of applications and are even used to manufacture production-quality parts in relatively small numbers. Rapid Prototyping is widely used in the automotive, aerospace, medical, and consumer products industries. In this paper are presented selected experimental test of materials used in different Rapid Prototyping Technologies. Main part of the paper is oriented on presentation of materials test of Fused Deposition Technology realized by authors on Department of Manufacturing Technology of Faculty of Manufacturing Technology in Presov (Slovakia).
Keywords: Rapid Prototyping; Fused Deposition Modelling; materials; experimental testing